2018
DOI: 10.21767/2248-9215.100064
|View full text |Cite
|
Sign up to set email alerts
|

Impression of Disparate Levels of Poultry Manure and Humic Acid on the Yield and Yield Traits of Maize (Zea Mays L.)

Abstract: Use of inorganic fertilizers have some problems to farmers in terms of high cost and short residual effect. Since use of organic fertilizers have a long residual effect but the nutrient requirement of crops is not fulfill in one season. So, using of combination of different organic manures can not only improve soil properties but also fulfill the nutrients requirement of crops. Therefore, a study was carried out aiming use of combinations of organic manures to improve maize yield and quality at the Cereal Crop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…As seen in Table 4, it was determined that the number of seeds per cob ranged from 342.27 pieces (control plot x DKC6050 variety) -287.87 pieces (the fourth dose of HA x DKC6664 variety). It was determined that the results of the study were consistent with the results of previous studies (Azeem et al, 2014;El-Saber et al, 2014;Moghadam et al, 2014;Hussain et al, 2018;Maruf and Mam-Rasul, 2019;Oktem and Oktem, 2020), which indicated that with the increase of HA doses the number of seeds per cob increased.…”
Section: Number Of Seeds Per Cobsupporting
confidence: 90%
See 1 more Smart Citation
“…As seen in Table 4, it was determined that the number of seeds per cob ranged from 342.27 pieces (control plot x DKC6050 variety) -287.87 pieces (the fourth dose of HA x DKC6664 variety). It was determined that the results of the study were consistent with the results of previous studies (Azeem et al, 2014;El-Saber et al, 2014;Moghadam et al, 2014;Hussain et al, 2018;Maruf and Mam-Rasul, 2019;Oktem and Oktem, 2020), which indicated that with the increase of HA doses the number of seeds per cob increased.…”
Section: Number Of Seeds Per Cobsupporting
confidence: 90%
“…The plant height increase associated with HA application may have been caused by the physiological effects of humic acid, including increased cell membrane permeability, acceleration of cell division, and root system development (Khaled & Fawy, 2011). Similar results that support these findings were demonstrated by Balbaa & Awad, 2013, Daur & Bakhashwain, 2013, El-Saber et al, 2014, Moghadam et al, 2014, Banitamim & Shokuhfar, 2017, Hussain et al, 2018, Aseres et al, 2019, and Hassan et al, 2019.…”
Section: Plant Heightsupporting
confidence: 56%
“…In another examination, utilization of poultry excrement either alone or coordinated with synthetic changes of P for maize, performed superior to anything all alterations tried in research facility trails [15]. Hussain A et al Prescribed that natural issue alone with manufactured manures could be useful for upgrading stale wheat grain yield, Therefore, prudent and efficient utilization of the current land, supplement composts application, budgetary assets and reusing of natural squanders under field conditions is unavoidable [16].…”
Section: Introductionmentioning
confidence: 99%
“…Kausar et al (2020) reported a significant increase in wheat (Triticum aestivum L.) yield by the addition of GYP and green manures. Improved yield and growth traits in maize (Zea mays L.) by the addition of PM and HA might be due to the addition of organic matter by these amendments, thus improving the physical, chemical, and biological properties of soil, and increasing nutrients availability within the rhizosphere zone, which consequently enhanced overall growth and yield attributes of peanut (Rizk et al 2012;Zhao et al 2016;Hussain et al 2018). Other possible explanations for the improved yield on applying amendments could be the enhanced soil moisture retention, which is directly linked with nutrients mobility and availability as found in present study with increased moisture percentage and nutrient content found in treatment where GYP and FYM applied in combination (Parihar et al 2019;Mariotte et al 2020).…”
Section: Discussionmentioning
confidence: 99%